Gender Differences in the Interrelations Among Social Support, Stressful Life Events, and Smoking Cessation in People With Severe Mental Illnesses. (March 2023) - Alghzawi, Hamzah M.; Storr, Carla L.
BACKGROUND: Social support and stressful life events (SLEs) have been found to be influential factors for smoking cessation in the general population, but little is known about these factors among smokers with severe mental illnesses (SMIs) and whether their associations with smoking cessation differ by gender. AIMS: To examine the association between social support and smoking cessation as mediated by SLEs in people with SMI and to examine whether the interrelations among social support, SLEs, and smoking cessation differ by gender. METHODS: A population sample of 4, 610 American lifetime adult smokers with schizophrenia, bipolar disorder, or major depressive disorder were identified in a limited public use data set of the 2012-2013 National Epidemiologic Survey on Alcohol and Related Conditions. Four mediation and moderated mediation models were used to examine gender differences in the interrelations among social support (total and three subscales of the Interpersonal Support Evaluation List–12), SLEs (summative score of positive responses to 16 types experienced in past year and related to health, job, death, or legal situations), and smoking status in prior year. RESULTS: Total, appraisal, and tangible support among females exerted indirect effects on smoking cessation via decreasing SLE scores. Among males, only belonging support exerted an indirect effect on smoking cessation via an increased SLE score. CONCLUSIONS: Findings suggest that interventions focusing on improving social support should be a priority for those working with smokers with SMI.